Technical Editor's Handbook : A Desk Guide for All Processors of Scientific or Engineering Copy - Freedman, George (Dover publications, Inc., 1994)
Anyone responsible for preparing scientific or technical copy for publication will find this comprehensive manual absolutely indispensable. It offers clear, easy-to-follow coverage of every important aspect of technical editing, from the very first steps to the final preparation of a manuscript for the printer. The book can help you spell, capitalize and abbreviate correctly, and deal confidently with prefixes and suffixes, subscripts, and Greek and Latin notations. It can help you set up equations with all their symbols and notations in correct form, order and position. It can even show how to use templates and simple drafting tools to draw symbols you don't have on your word processor or type writer keyboard. To better prepare you in a given subject area, the "Technical Editor's Handbook" clearly and succinctly introduces the basic principles of five of the most commonly encountered disciplines. Individual chapters offer short courses in the fundamentals of mathematics, computers, physics, electricity and electronics, an chemistry. Every attempt has been made to present this material in a nontechnical style easily understandable to the nonspecialist. This comprehensive, easy-to-use guide includes an exhaustive, fully cross-referenced index and a table of contents that outlines in full detail all the topics and the correct spelling, meaning, syllabic division, part of speech and abbreviation of several thousand technical terms. And its 18 glossaries show and tell at a glance numerical prefixes, mathematical signs and symbols, computer flowchart symbols and other highly useful information.